Indonesian Tax Law Reform to Encourage Sustainable Economic Growth - Rasji, Rasji; Beale, Aurelius Steven; Simarmata, Michael Kalep (CV. Rayyan Dwi Bharata, 2023)
Indonesia's state tax functions as a means of collecting state revenue, also known as the budget, and has a regulatory function. MSMEs are key tools to achieve the Sustainable Development Goals. It is considered an economic engine used as the main tool to reduce poverty through promoting sustainable development projects. The success of MSMEs in growing the national economy is evident in their financial performance reports. The research methodology presented in this article uses an interpretive analysis of the concepts presented in this article by applying a three-dimensional model to discuss tax reform. The result of this study is that the lower the level of tax incentives granted, the better the financial performance of MSMEs. The existence of tax incentives for MSMEs improves financial performance in the form of net realized profits. Tax incentives are a form of tax reduction in the form of reduced tax rates for taxpayers who meet certain conditions to minimize the tax burden.